Temperature sensitivity of oxygen demand varies as a function of organic matter source - Szewczyk, Curtis J.; Smith, Erik M.; Benitez-Nelson, Claudia R. (Frontiers in Marine Science, 2023)
Dissolved oxygen (DO) impairment within coastal waters is widespread and rising temperatures may exacerbate low DO levels by enhancing organic matter (OM) degradation. Here, the temperature sensitivity of OM degradation was investigated as DO decay rates determined during standard five-day biochemical oxygen demand (BOD) measurements conducted under different incubation temperatures. Sampling was conducted in the Waccamaw River watershed, South Carolina, a blackwater river with extensive forested wetland that also receives drainage from stormwater detention ponds associated with coastal development, thus providing different sources of contrasting OM composition. Temperature sensitivities were measured as Q10 temperature coefficients, which define how DO decay rates change with 10 degrees of warming. The average Q10 value for the wetland sites (2.14 ± 0.41) was significantly greater (p < 0.05) than those measured in either the River (1.49 ± 0.36) or stormwater ponds (1.41 ± 0.21). Furthermore, using Intergovernmental Panel on Climate Change intermediate-to-very high temperature estimates for 2100 of +2.7 – 4.4°C, average predicted increases in DO decay rates for wetlands ( 22-39%) are more than double the River ( 11-18%) and stormwater pond rates ( 9-16%). Our findings for inland, coastal waters agree with previous results for soils, suggesting that temperature sensitivities are variable across sites and increase with more complex, lower quality OM. Future modeling scenarios of DO utilization must therefore consider the influence of OM heterogeneity and the temperature sensitivity response of OM degradation across sources and region to better predict how climate change may impact oxygen impairment in aquatic ecosystems.